The cost-effectiveness of bisphosphonates in postmenopausal women based on individual long-term fracture risks. - van Staa, T; Kanis, J; Geusens, P; Boonen, A; Leufkens, H; Cooper, C (2007)
OBJECTIVES: Cost-effectiveness analyses are routinely based on data from group averages, restricting its generalizibility to those with below- or above-average risk. A pharmaco-economic model that used individualized risks for fractures was developed in order to take into account patient heterogeneity. METHODS: Data were obtained from The Health Improvement Network research database of general practitioners, comprising a UK general population of women aged more than 50 years (N = 330,000). Mortality and hip, vertebral, and other osteoporotic fracture risks for each individual were estimated by age, body mass index (BMI), smoking, and other clinical risk factors. Estimates on costs, EuroQol (EQ-5D) utilities, and treatment efficacy were obtained from a UK national report (the National Institute for Clinical Excellence) and outcomes were simulated over a 10-year period. RESULTS: It was found that the cost per quality-adjusted life-year (QALY) gained was lower in elderly women and in women with fracture history. There was a large variability in the cost-effectiveness with baseline fracture risk and with clinical risk factors. Patients with low BMI (<20) had considerable better cost-effectiveness than patients with high BMI (>or=26). Using a cost-acceptability ratio of 30k pounds per QALY gained, bisphosphonate treatment became cost-effective for patients with a 5-year risk of 9.3% (95% confidence interval [CI] 8.0-10.5%) for osteoporotic fractures and of 2.1% (95% CI 1.5-2.7%) for hip fractures. Including bone mineral density in the risk assessment, the cost per QALY gained was 35k pounds in women at age 60 with a fracture history and a T-score of -2.5 (at age 80, this was 3k pounds). CONCLUSION: A pharmacoeconomic model based on individual long-term risks of fracture improves the selection of postmenopausal women for cost-effective treatment with bisphosphonates.